2022
DOI: 10.1002/nop2.1444
|View full text |Cite
|
Sign up to set email alerts
|

Health as expanding consciousness: Change of psychological situation in nursing students

Abstract: Aim This study aims to explore the mind of Chinese nursing students transitioning to online education in the pandemic using health as expanding consciousness (HEC) as methodology. Design A qualitative, descriptive study based on interviews. Methods This qualitative study was conducted from September to November 2021 by students in the Guangzhou university of Chinese medicine. Thirteen participants were recruited using purposive sampling. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Studies have found that intrinsic individual consciousness predicts psychological resilience. Individual consciousness refers to individual perceptions and attitudes about what one does, including awareness of one's own existence and relationship with people or objects around oneself [ 10 ]. Individual consciousness consists of intrinsic self-awareness and extrinsic perceived behaviors [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that intrinsic individual consciousness predicts psychological resilience. Individual consciousness refers to individual perceptions and attitudes about what one does, including awareness of one's own existence and relationship with people or objects around oneself [ 10 ]. Individual consciousness consists of intrinsic self-awareness and extrinsic perceived behaviors [ 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous studies related to psychological resilience, it was generally believed that psychological resilience is influenced by individual and environmental factors, such as self-efficacy, natural environment, educational level, and trauma experience [ [6] , [7] , [8] , [9] ]. However, these studies have not fully explored the influence of individual consciousness on psychological resilience, which includes internal self-awareness and external perceived behavior, especially in a situation of collective pressure, such as a public crisis [ 10 , 11 ]. It has been proved that individual consciousness has great significance for psychological resilience.…”
Section: Introductionmentioning
confidence: 99%